The Development of Accounting Clinics at Islamic Religious Higher Education Institutions (PTKI) in Indonesia - Iwan Setiawan; Abdulah Safei; Dudang Gojali; Nurhaeti Nurhaeti; Rahayu Kusumadewi (Fakultas Ekonomi dan Bisnis Islam, 2025)
This study aims to analyze the development of accounting clinics at Islamic religious universities (PTKI) in Indonesia. Researchers use descriptive analytic techniques in conjunction with qualitative approaches to produce a comprehensive picture. Research data sources are primary data sources and successful data. Data analysis techniques include data collection, data reduction, data display, conclusion drawing. The results showed that the operational mechanism of the Accounting Clinic at Islamic Religious Universities (PTKI) consisted of manual and computer practice guided by lab lecturers. for this reason, the clinic collaborates with several partners, namely the Public Accounting Firm (KAP), the ministry, the local government, and several private companies. The accounting clinic aims to provide students with an understanding of the application of accounting concepts in real-world business practices. In order to work and carry out the function of accounting technician services professionally, the workforce involved in this field must have a competency base of national and international standards. This can be achieved through education, training, and experience in order to improve the competence of accounting technicians which includes knowledge, skills, and attitude. This research has implications for all PTKIN that have accounting study programs to maximize accounting clicks so that they can produce quality graduates so that they are ready to enter the world of work.